Trends in infant nutrition in Saudi Arabia: compliance with WHO recommendations - El Mouzan, Mohammed I. (Medknow Publications, 2009)
BACKGROUND AND OBJECTIVE: The WHO recommends exclusive breastfeeding in the first 6 months of life. Our objective was to evaluate trends in infant nutrition in Saudi Arabia and the degree of compliance with WHO recommendations. SUBJECTS AND METHODS: A nationwide nutritional survey of a sample of Saudi households was selected by the multistage probability sampling procedure. A validated questionnaire was administered to mothers of children less than 3 years of age. RESULTS: Of 5339 children in the sample, 4889 received breast milk at birth indicating a prevalence of initiation of 91.6%. Initiation of breastfeeding was delayed beyond 6 hours after birth in 28.1% of the infants. Bottle feeding was introduced by 1 month of age to 2174/4260 (51.4%) and to 3831/4260 (90%) by 6 months of age. The majority of infants 3870/4787 (80.8%) were introduced to “solid foods” between 4 to 6 months of age and whole milk feedings were given to 40% of children younger than 12 months of age. CONCLUSIONS: The current practice of feeding of Saudi infants is very far from compliance with even the most conservative WHO recommendations of exclusive breastfeeding for 4 to 6 months. The high prevalence of breastfeeding initiation at birth indicates the willingness of Saudi mothers to breastfeed. However, early introduction of complementary feedings reduced the period of exclusive breastfeeding. Research in infant nutrition should be a public health priority to improve the rate of breastfeeding and to minimize other inappropriate practices.